Asymptomatic falciparum malaria and genetic polymorphisms of Pfcrt K76T and Pfmdr1 N86Y among almajirai in northeast Nigeria - Balogun, Sulayman Tunde; Sandabe, Umar Kyari; Bdliya, Dauda N.; Adedeji, Waheed A.; Okon, Kenneth O.; Fehintola, Fatai A (The Journal of Infection in Developing Countries, 2016)
Introduction: Malaria remains a public health challenge, especially in sub-Saharan Africa where asymptomatic malaria is not uncommon. In the present study, the prevalence of asymptomatic falciparum malaria was investigated in almajirai, and the genetic polymorphisms of chloroquine (CQ) resistance biomarkers were assessed. Methodology: A total of 440 apparently healthy almajirai between 3 and 12 years of age were randomly enrolled in Maiduguri, northeast Nigeria, between July and December 2010. Parasitemia and gametocytemia were assessed by light microscopy, and polymorphisms of Pfcrt K76T and Pfmdr1 N86Y were detected by nested polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) techniques. Results: The mean age of the subjects was 8.3 ± 4.5 years, with subjects ≤ 5 years accounting for 10.7% (47/440) of the population. Prevalence of asymptomatic falciparum parasitemia and gametocytemia were 12.7% (56/440) and 8.6% (38/440), respectively. Geometric mean parasite density (GMPD) was 240 (160–630) parasites/µL, while geometric mean gametocyte density (GMGD) was 53 (24–96) gametocytes/µL. The GMPD was higher among subjects ≤ 5 years of age (p = 0.027). Pfcrt 76T was detected in 5.4% (3/56) of the isolates, and no isolates harbored Pfmdr1 86Y mutant. Conclusions: The study reveals asymptomatic falciparum malaria in almajirai and low levels of Pfcrt 76T and Pfmdr1 86Y alleles. These findings could hinder malaria control measures, and hence almajirai should be incorporated into malaria control programs.